If,

Sachin + Ramesh + Tendulkar = 6

Sachin x Ramesh = 2

Ramesh x Tendulkar = 6

Then,

Tendulkar x Sachin =?

Answer:

Let Sachin = 's', Ramesh = 'r' and Tendulkar = 't'

Then,

s+r+t = 6

s * r = 2

r * t = 6

Now if 6 s*r = 6; s * r = 1 or s = r = 1 and therefore t = 4.

And therefore Tenulkar x Sachin = 4x1 = 4.

Sachin + Ramesh + Tendulkar = 6

Sachin x Ramesh = 2

Ramesh x Tendulkar = 6

Then,

Tendulkar x Sachin =?

Answer:

Let Sachin = 's', Ramesh = 'r' and Tendulkar = 't'

Then,

s+r+t = 6

s * r = 2

r * t = 6

Now if 6 s*r = 6; s * r = 1 or s = r = 1 and therefore t = 4.

And therefore Tenulkar x Sachin = 4x1 = 4.